2021
DOI: 10.21273/hortsci15180-20
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Growth and Nutritional Quality of Two-leaf-color Pak Choi by Supplemental Alternating Red and Blue Light

Abstract: The aim of the present study was to evaluate the effects of alternating red (660 nm) and blue (460 nm) light on the growth and nutritional quality of two-leaf-color pak choi (Brassica campestris L. ssp. chinensis var. communis). Four light treatments (supplemental alternating red and blue light with intervals of 0, 1, 2, and 4 hours, with a monochromatic light intensity of 100 μmol·m−2·s−1 and a cumulative lighting time of 16 hours per day) were conducted in a greenhouse under identical ambient light condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Simultaneous irradiation RB16 induced larger leaf width compared with interchanging irradiation R4/B4 and R8/B8. Our findings were not consistent with results reported by Shimokawa et al (2014), Ohtake et al (2018) and Huang et al (2021), in which, interchanging irradiation Rand B-LED irradiation induced plant growth compared to simultaneous RB16. The discrepancies might be attributed to inadequate light intensity under RB and R/B.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Simultaneous irradiation RB16 induced larger leaf width compared with interchanging irradiation R4/B4 and R8/B8. Our findings were not consistent with results reported by Shimokawa et al (2014), Ohtake et al (2018) and Huang et al (2021), in which, interchanging irradiation Rand B-LED irradiation induced plant growth compared to simultaneous RB16. The discrepancies might be attributed to inadequate light intensity under RB and R/B.…”
Section: Discussioncontrasting
confidence: 99%
“…This occurs because of light dispersing out from the front portion of the growth chamber (refer to Figure 1). In contrast, the combined R-and B-light PPFD used in other similar studies (Huang et al, 2021;Ohtake et al, 2018;Shimokawa et al, 2014) were around more than 100 µmol•m −2 •s -1 . The limitation of PPFD in our experimental setup may be restricted to the RGB LED strips installed in our growth chamber.…”
Section: Discussionmentioning
confidence: 68%
“…In general terms, red light promotes photosynthesis and improves vegetative growth by increasing the chlorophyll content, and blue light is absorbed by carotenoid pigments, favoring the opening of the stomas [9]. In this sense, also, Huang et al [32] have recently shown that a 4 h interval of supplemental red and blue lights (16 h in total: 1250 kJ m −2 ), alternatively applied, improves the accumulation of phenolic compounds and carotenoids in green-leaf and red-leaf pak choi. However, the ratio of red and blue light must be optimized for each species [38].…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies found that the combination of blue and red lights, both simultaneously [31] and separately [32], increased the total phenolic content by improving photosynthesis, as well as the malonyl-CoA production, which is associated with the synthesis of phenolic compounds. In this sense, our results demonstrate for the first time that the application of blue and red LED lighting in separate phases of the light cycle during carrot sprouting improved the total phenolic content.…”
Section: Discussionmentioning
confidence: 98%
“…Crop growth and development are influenced by climate conditions, which also have an impact on how well-balanced the diet of crops is. Huang et al showed that the growth of leaves of two-leaf Chinese cabbage irradiated alternately with red and blue light was better than that of control treatment, moreover, red and blue light irradiation had an effect on the concentration of chla, total chlorophyll, carotenoids, soluble protein and so on [ 20 ]. In addition, Anza et al showed that the season had an effect on the nutritional quality parameters of tomatoes, and the nutritional quality of tomatoes grown in spring was better [ 21 ].…”
Section: Factors Influencing the Nutritive Value Of Farm Commoditiesmentioning
confidence: 99%